Parasitic nematodes of wild and cultivated subtropical fruit plants in Central Asia - Sh. Kh. Khurramov; A. S. Bekmuradov (Российский паразитологический журнал, 2021)
The purpose of the research is studying the species composition and control measures against parasitic nematodes of wild and cultivated subtropical fruit plants of Central Asia.Materials and methods. We studied subtropical fruit crops in 198 farms and 1985 household plots located in various soil and climatic zones of over 20,675 hectares in Central Asia. The materials were collected in the autumn (September-October), spring (April-May) and summer (June-August) months in 1970–1990 by the route method. Study subjects were plant parasitic nematodes of 8 species of wild and cultivated subtropical fruit plants in the Central Asian republics. A modified Baermann funnel method was used to isolate plant nematodes from plants and soil near roots. In total, we collected and analyzed more than 5,400 plant and soil samples. To identify the species of plant parasitic nematodes, we used the Atlas of plant parasitic nematodes compiled at the Institute of Parasitology of the Russian Academy of Sciences, as well as morphometric indicators obtained according to the generally accepted De Mann formulae.Results and discussion. More than 129,000 specimens of plant parasites of 98 species were found in the studied wild and cultivated subtropical fruit crops and soil near their roots. In many farms of the Central Asian republics, we found southern root-knot nematodes, peanut root-knot nematodes, javanese root-knot nematodes, and cotton root-knot nematodes in mixed populations. In Uzbekistan, the prevalence in these crops was from 8 to 61.3%, in Tajikistan – from 78 to 98%, in Turkmenistan – from 6 to 98%, and in Kyrgyzstan – 33%. In addition to root-knot nematodes, representatives of ecto- and endoparasites of the genera Tylenchorhynchus, Merlinius, Quinisulcius, Rotylenchus, Helicotylenchus, Pratylenchus, Paratylenchus, Macroposthonia, Labocriconema and Xiphinema were parasitizing in the above subtropical cultures. Under production conditions, we tested Furadan at a dose of 40 kg/ha, Heterophos at a dose of 60 and 120 kg/ha, and Aldicarb at a dose of 40 kg/ha to control root-knot and other parasitic nematodes. Their efficacy ranged from 89 to 100%. We also used the soil solarization method developed by us, the efficacy of which was 95–98%.